ANALISIS PERAN GAMIFIKASI DALAM MENINGKATKAN MOTIVASI SISWA DALAM PROGRAM BIMBINGAN KARIR - Hermayesi, Hermayesi; Fitriani, Wahidah (STKIP Pesisir Selatan, 2024)
The application of gamification in career guidance programs has the potential to change the way students view and engage with the program. With strategically designed game elements, gamification can help students feel more motivated, increase their participation, and encourage them to plan their future careers more seriously. This study aims to analyze the role of Gamification in increasing student motivation in Career Guidance Programs at the high school level. The qualitative approach used aims to explore the experiences and perspectives of students and guidance and counseling teachers in the career guidance program. Data were collected through in-depth interviews, participatory observation, and document analysis. The results showed that the application of gamification elements such as point awarding, leaderboards, and weekly challenges in the Career Guidance Program was able to increase students' participation, engagement, and awareness of their future career planning after high school. Gamification provides an interactive and fun learning environment, which has a positive impact on students' intrinsic and extrinsic motivation in planning for a bright future.